Noongar Dandjoo: A Work Integrated Learning Case Study - Johnston, Michelle; Bishop, Russell (Sage Pulbications, 2013)
As media employers increasingly shift the burden for the provision of skills training from themselves to universities, academics must develop innovative ways to ensure their graduates are truly job ready, beyond merely simulating industry practice and offering conventional work experience opportunities. Under the umbrella term Work Integrated Learning (WIL), universities have adopted a range of educational approaches that combine theory with practice to enhance learning experiences for students. But not all WIL initiatives are the same and nor do they always achieve their objectives. However, three series of the award-winning student TV production Noongar Dandjoo, produced by Curtin University, offer a new model for teaching substantive journalism, program production as well as cultural aware- ness and cultural sensitivity under an offshoot of WIL called service-learning. As this article seeks to demonstrate, Noongar Dandjoo is making a lasting and positive impression on students who are applying their experiences working with indigenous people beyond university.